Larvicidal and Enzymatic Inhibition Effects of Annona Muricata Seed Extract and Main Constituent Annonacin against Aedes Aegypti and Aedes Albopictus (Diptera: Culicidae) - Alzeir Machado Rodrigues; Antonio Adailson Sousa Silva; Cleonilda Claita Carneiro Pinto; Dayanne Lima dos Santos; José Claudio Carneiro de Freitas; Victor Emanuel Pessoa Martins; Selene Maia de Morais (MDPI AG, 2019)
The mosquitoes Aedes aegypti and Aedes albopictus are vectors of arboviruses that cause dengue, zika and chikungunya. Bioactive compounds from plants are environmentally sustainable alternatives to control these vectors and thus the arboviruses transmitted by them. The present study evaluated the larvicidal activity of an acetogenin-rich fraction (ACERF) and its main constituent annonacin obtained from Annona muricata seeds on Ae. aegypti and Ae. albopictus. The larvicidal assays were performed using different concentrations to calculate the LC50 and LC90 values observed 24 h after exposure to the treatment. Annonacin was more active against Ae. aegypti (LC50 2.65 μg·mL−1) in comparison with Ae. albopictus (LC50 8.34 μg·mL−1). In contrast, the acetogenin-rich fraction was more active against Ae. albopictus (LC50 3.41 μg·mL−1) than Ae. aegypti (LC50 12.41 μg·mL−1). ACERF and annonacin treated larvae of Ae. aegypti and Ae. albopictus showed significant differences in the inhibition of their metabolic enzymes when compared to untreated larvae. The results demonstrate the relevant larvicidal action of the acetogenin-rich fraction and annonacin showing the potential to develop new products for the control of Ae. aegypti and Ae. albopictus.